Brand rituals [ how successful brands bond with customers for life - Raj, Zain (Spyglass Pub., 2012)
In Brand Rituals: How Successful Brands Bond with Customers for Life, Zain Raj--a recognized leader in the marketing and strategy space--posits that companies and their brands have the ability to drive significant business impact by creating a bond with their most loyal customers. Raj calls this a Brand Ritual, a deep, abiding relationship that customers build with brands--which becomes an integral part of their lives. The book discusses how it's no longer